LIPID PRODUCTION FROM BR. 2.2 OLEAGINOUS FUNGAL ISOLATE USING ACETATE, GLYCEROL, AND MOLASSES AS CARBON SOURCES - Chikmatul Alifiyatin; Salma Darmayanti; Wanny Firdasi; Miftahul Ilmi (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Microorganisms that accumulate more than 20% of their dry cell weight as lipids are called oleaginous microorganisms. Oleaginous microorganisms can grow well on various carbon sources other than glucose. These non-glucose alternative carbon sources could potentially reduce high biofuel manufacturing costs. BR. 2.2 isolate is an oleaginous fungus that accumulates 0.62 g L-1 lipids using glucose as a carbon source. This study aims to determine the effect of acetate, glycerol, molasses, and C/N ratios on lipid accumulation of the BR.2.2 isolate. The highest lipid produced by the BR. 2.2 isolate using acetate is 0.196 g L-1 at a C/N ratio of 400, 0.229 g L-1 at a C/N ratio of 225 using glycerol, and 1.97 g L-1 at a C/N ratio of 25 using molasses in 144 hours of incubation. The results revealed that the accumulation of lipids increased with the rising acetate and glycerol C/ N ratios and incubation period. Meanwhile, the accumulation of lipids decreased with increasing molasses C/N ratio.